Whether optimum pollen germination and tube length attained in the same growth medium (sucrose + 2,4-D) by five cultivars of the Apocynaceae : Further Evidence of a Criticism of Banerji and Gangulee (1937), Brewbaker and Kwack’s (1963), Sudhakaran (1967- - S. A. Salgare (Environment Conservation Journal, 2006)
All the different concentrations of simazine tried suppressed the  germination  of pollen  of  F-72  series of  pink-flowered cultivar of Catharanthus roseus. The  widest range  of concentrations of 2,4-D were proved to be  10-17-  40 and 10-17-100  mg/ ml which stimulated the  pollen germination and tube  growth respectively of successive flowers of the Apocynaceae. Tube length in vitro is 9.54% in F-48 series of pink-flowered cultivar of C. roseus of the tube length found in vivo is the longest of all the cultivars investigated of Apocynaceae